2011
DOI: 10.1038/oby.2009.452
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence for the Role of Human Adenovirus‐36 in Obesity in a European Cohort

Abstract: EpidEmiologyIn 2001, the possibility of an infectious component in the etiology of obesity was raised by Dhurandhar introducing the term "infectobesity" (1). In particular, support for Adenovirus type 36 (Ad-36) as a contributor to the obesity epidemic was found in chickens, mice and nonhuman primates (1-6). In 2005, a significant (relative risk = 2.7, P < 0.001) association between obesity and the presence of Ad-36 neutralizing antibodies in human serum was described in the United States by Atkinson et al. (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 13 publications
2
60
3
1
Order By: Relevance
“…In this regard, Ad-36 seropositivity increases from o5% in subjects up to 30 years of age to 410% in those over 50 years in the Netherlands and Belgium. 10 Nonetheless, we failed to find any increase in Ad-36 seropositivity in obese subjects with age (28.6% in schoolchildren and 30% in adults). At present, it is not known if an age-specific increase in Ad-36 seropositivity occurs only in normal Korean individuals.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In this regard, Ad-36 seropositivity increases from o5% in subjects up to 30 years of age to 410% in those over 50 years in the Netherlands and Belgium. 10 Nonetheless, we failed to find any increase in Ad-36 seropositivity in obese subjects with age (28.6% in schoolchildren and 30% in adults). At present, it is not known if an age-specific increase in Ad-36 seropositivity occurs only in normal Korean individuals.…”
Section: Discussionmentioning
confidence: 42%
“…A study of Dutch and Belgian people found that Ad-36 infection was unlikely to be associated with obesity. 10 Another recent study showed no association between Ad-36 seropositivity and US military personnel. 11 The reasons for these inconsistent results are not known.…”
Section: Introductionmentioning
confidence: 99%
“…These research studies provide considerable data to support infectobesity, but some studies do not agree with the concept, such as the Dutch and Belgian epidemiological studies (50).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Ad36 infection increases body weight, fat deposition, and insulin sensitivity, but decreases cholesterol and triglyceride levels (40,42,43). In contrast, several studies found no relationship between Ad36 seropositivity and human obesity, including, Dutch, Belgian (50), and USA military studies (51). All epidemiological studies of Ad36 are cross-sectional studies.…”
Section: Adenovirus 36mentioning
confidence: 99%
“…Obesity is a chronic disease with multiple etiology including also such non-dietary factors as a viral and bacterial infection [17,18,20,[23][24][25]. Recently, the evidences on the adenovirus infection related obesity where confirmed in adult patients from USA [26][27][28], Italy [28], Korea [29] and in pediatric subjects from Korea [30,31], but not fully validated association was observed in studies on Belgium and Dutch obese persons [32,33]. Thus, the aim of our pilot study was to investigate the possible role of human adenovirus infection in etiology of obesity in the sample cohort of adult female subjects recruited from typical middle-sized urban area in Poland.…”
Section: Introductionmentioning
confidence: 99%